Exploring machine learning techniques for symptom-based detection of livestock diseases - Niloy, Mahir Ahmed; Bhowmik, Tanmay; Abedin, Jennifer; Ferdous, Syeda Jannatul; Jahan, Ishrat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.